Cubozoan crystallins: evidence for convergent evolution of pax regulatory sequences - Kozmik, Zbyněk; Swamynathan, Shivalingappa K; Růžičková, Jana; Marková, Kristýna; Pačes, Václav; Vlček, Čestmír; Piatigorsky, Joram (Evolution & development, 2008)
Cnidaria is the earliest-branching metazoan phylum containing a well-developed, lens-containing visual system located on specialized sensory structures called rhopalia. Each rhopalium in a cubozoan jellyfish Tripedalia cystophora has a large and a small complex, camera-type eye with a cellular lens containing distinct families of crystallins. Here, we have characterized J2-crystallin and its gene in T. cystophora. The J2-crystallin gene is composed of a single exon and encodes a 157-amino acid cytoplasmic protein with no apparent homology to known proteins from other species. The non-lens expression of J2-crystallin suggests nonoptical as well as crystallin functions consistent with the gene-sharing strategy that has been used during evolution of lens crystallins in other invertebrates and vertebrates. Although nonfunctional in transfected mammalian lens cells, the J2-crystallin promoter is activated by the jellyfish paired domain transcription factor PaxB in co-transfection tests via binding to three paired domain sites. PaxB paired domain-binding sites were also identified in the PaxB-regulated promoters of the J1A- and J1B-crystallin genes, which are not homologous to the J2-crystallin gene. Taken together with previous studies on the regulation of the diverse crystallin genes, the present report strongly supports the idea that crystallin recruitment of multifunctional proteins was driven by convergent changes involving Pax (as well as other transcription factors) in the promoters of nonhomologous genes within and between species as well as within gene families.
Keywords: Cubozoa; molekulární evoluce; Chlorocebus aethiops; exony; Humans; Promoter Regions, Genetic; sekvence nukleotidů; regulace genové exprese; Molecular Sequence Data; klonování DNA; Evolution, Molecular; molekulární sekvence - údaje; Paired Box Transcription Factors; COS Cells; financování organizované; Exons; Lens, Crystalline; vazebná místa; lidé; Financing, Organized; zvířata; Binding Sites; buněčné linie; Cercopithecus aethiops; COS buňky; Gene Expression Regulation; Cell Line; Base Sequence; Crystallins; Cytoplasm; krystaliny; cytoplazma; Animals; transkripční faktory paired box; Cloning, Molecular; oční čočka; promotorové oblasti (genetika)